Exploring the role of the core in sports performance: a systematic review of the effects of core muscle training - Bustos Carvajal, J. S.; Arias Coronel, F. (Frontiers in Sports and Active Living, 2025)
Introduction: The Core or central area of the body, is a group of muscles in charge of providing stability and postural control, being crucial in sports performance. In sports, the practice of exercises to strengthen this region can improve different performance variables. However, most of these programs in athletes focus on direct and specific strengthening of the extremities, largely ignoring the role that this part of the body can have on strength and power. Therefore, the aim of this study is to systematically review the literature on the effects of core muscle training on key athletic performance parameters in competitive athletes, focusing primarily on core strength, dynamic balance, sprint speed, jump height, and agility.